Analisis Kapasitas Produksi dengan Pendekatan Promodel di PT Asahimas Flat Glass tbk - Muhammad Ihsan; Diki Muchtar; Davito Arnanta Putra (Jurnal Teknologika, 2026)
This study analyzes production capacity improvement at PT Asahimas Flat Glass Tbk using discrete-event simulation with ProModel. Empirical data were collected through observations, time studies, interviews, and production records to develop and validate a simulation model that reflects actual production conditions. Initial simulations identified a bottleneck in the assembly process, limiting output to 35 units per hour. Two improvement scenarios were evaluated, with the second alternative involving the addition of one operator at the assembly workstation. Results showed a significant increase in production output to 78 units per hour, with a moderate increase in operational costs from Rp 21,100,000 to Rp 24,600,000. These findings confirm that appropriate labor allocation based on simulation analysis effectively improves production performance and manufacturing efficiency.